1980s–2010s: The world's largest mangrove ecosystem is becoming homogeneous. (August 2019) - Sarker, Swapan Kumar; Matthiopoulos, Jason; Mitchell, Sonia N.; Ahmed, Zahir Uddin; Mamun, Md. Bashirul Al; Reeve, Richard
Abstract: Knowledge gaps in spatiotemporal changes in mangrove diversity and composition have obstructed mangrove conservation programs across the tropics, but particularly in the Sundarbans (10, 017 km 2 ), the world's largest remaining natural mangrove ecosystem. Using mangrove tree data collected from Earth's largest permanent sample plot network at four historical time points (1986, 1994, 1999 and 2014), this study establishes spatially explicit baseline biodiversity information for the Sundarbans. We determined the spatial and temporal differences in alpha, beta, and gamma diversity in three ecological zones (hypo-, meso-, and hypersaline) and also uncovered changes in the mangroves' overall geographic range and abundances therein. Spatially, the hyposaline mangrove communities were the most diverse and heterogeneous in species composition while the hypersaline communities were the least diverse and most homogeneous at all historical time points. Since 1986, we detect an increasing trend of compositional homogeneity (between-site similarity in species composition) and a significant spatial contraction of distinct and diverse areas over the entire ecosystem. Temporally, the western and southern hypersaline communities have undergone radical shifts in species composition due to population increase and range expansion of the native invasive species Ceriops decandra and local extinction or range contraction of specialists including the globally endangered Heritiera fomes . The surviving biodiversity hotspots are distributed outside the legislated protected area network. In addition to suggesting the immediate coverage of these hotspots under protected area management, our novel biodiversity insights and spatial maps can form the basis for spatial conservation planning, biodiversity monitoring and protection initiatives for the Sundarbans. Highlights: We uncover spatiotemporal changes (1986–2014) in mangrove biodiversity in the Sundarbans. Biotic homogenization has been underway in the Sundarbans. Drastic loss of biomass-productive species suggests declining ecosystem carbon stock. Hypersaline areas experienced highest turnover in species composition. The Protected Area Network does not include the biodiversity hotspots, and hence requires reconfiguration.